Anisotropy in Some Alluvial Soils - Phonate, V; Malik, R S; Kumar, Sanjay (Annals of Arid Zone, 2016)
Saturated hydraulic conductivity in vertical (KY) and horizontal (KH) directions were experimentally determined for different soil depths, i.e., 0.05 to 0.10 m, 0.15 to 0.20 m and 0.25 to 0.30 m in three alluvial soils. KH was found to be larger than KY in all soils and at all depths by a factor ranging from 1.1 to 7.2. Overall average of KH/KY ratio for all soils and depths was 2.1. There was no corresponding anisotropy in compaction in any of the soils. Higher bulk densities encountered in deeper layers indicated the formation of plough layer.